Menghuni Lumbung: Beberapa Pertimbangan Mengenai Asal-Usul Konstruksi Rumah Panggung di Kepulauan Pasifik - Koji Sato (Antropologi Indonesia, 1991)
The architecture of stilt house - as the form of traditional house - in pacific region shows some basic similarities. House constructions that consist of bottom structure-primary structure - top structure are in accordance with cosmic classification, i.e. lower world - human world - upper world. In this comparative study, the author tries to show that stilt-house basically is the development of granary architecture. In many societies granary is a sacred place where occasional rituals are undertaken. The couch underneath the granary is often used for activities even for living places. The author argues that formerly people lived in granary and then changed to be stilt-house. Using some examples from various ethnic groups in the Philippines, Japan, New Zealand and Indonesia he explains that the attic id a place for gods and sacred things.